The Spiritual Values of Gratitude Concept in Tafsir Al-Misbah in the Perspective of Spiritual Well-Being - Nur Kholik Afandi; Anis Komariah (Potret Pemikiran, 2021)
Gratitude in Islamic teachings includes three aspects: gratitude with heart, verbal, and deed. Therefore, gratitude is limited to verbal recognition in the heart and should be realized in concrete actions (Tafsir al-Miṣbāḥ). In Positive Psychology, gratitude has three functions: a barometer, motivator, and moral reinforcement. Through a hermeneutic approach, the purpose of this study is to explore 1) the spiritual values of the concept of gratitude in Tafsir al-Miṣbāḥ and, 2) How is the relevance of the spiritual values of gratitude in Tafsir al-Miṣbāh in creating spiritual well-being. This research is a literature study, with the primary data source being the verses of the Qur'an about gratitude described in the Tafsir al-Misbah interpretation. Through a hermeneutic approach, the study results show that gratitude is a Spiritual Capital in creating spiritual well-being. Gratitude contains psycho-spiritual values such as trust (Amanah), satisfaction (qanā‘ah), humility (tawāḍu'), and optimism. These values function as motivation and morale reinforcement to build harmonious relationships between individuals, others, the universe, and God (spiritual well-being).Keywords: Spiritual Well-being; Gratitude Concept; Gratitude Spirituality.